Risks to the clinician of risk management: recalled and anticipated consequences of decision-making - Challinor, Alexander; Bhandari, Sahil; Boyle, Sean; Gabbay, Mark; Wilson, Pete; Saini, Pooja; Nathan, Rajan (Frontiers in Psychiatry, 2025)
BackgroundDespite extensive literature studying how we make decisions in the face of uncertainty, the empirical study of real-world clinical decision-making in mental health practice remains limited. Decisions in clinical settings are not just made on the basis of clinical factors. A key non-clinical influence on decision making is the clinician’s concerns about the ‘threat’ to themselves from a future adverse incident and the subsequent retrospective scrutiny of their decision-making. A better understanding of non-clinical processes is essential to inform better ways of guiding effective decision-making. More specifically, delineating the nature of this ‘threat’ process will also inform approaches to patient safety.AimsThe objective of the current study was to delineate consequences recalled and anticipated by mental health clinicians making decisions under uncertainty.MethodsThis was an analysis of data arising from six focus group discussions with professionals involved in decisions to admit patients to psychiatric hospitals (consultant psychiatrists, approved mental health practitioners, crisis resolution home treatment teams, and liaison psychiatry practitioners) in one National Health Service Trust, UK. The data were thematically analyzed to identify the nature of ‘threat’ processes that arise in clinical decision-making.ResultsThemes identified included (i) the location of the effect of the anticipated/recalled consequence(s), (ii) the location of the origin of the consequence, and (iii) the nature of the consequence. The recalled and anticipated consequences of decision-making were overwhelmingly, but not exclusively, negative. The consequences were largely perceived to be directed towards the self (i.e., the clinician) and were considered to originate from external scrutiny by peers, organizational leadership, and the patient safety system/processes.ConclusionsThe process of making decisions to admit patients to hospital consistently involved the decision-maker’s concern with the future consequences for them, either from a prior or future adverse event. The findings of this study, alongside other evidence of the complexity of decision-making, have implications for improving and studying clinical decision-making (and, by extension, patient care and outcomes), patient safety responses, and professional well-being.